Clinical and etiological profile of unprovoked thrombosis in young patients admitted at a tertiary care hospital - Ahmad, Nadeem; Akhter, Nihida; Sheikh, Tufail Ahmad (International Journal of Research in Medical Sciences, 2017)
Background: It is now possible to identify acquired and hereditary risk factors in a substantial percentage of patients presenting with a venous thrombotic event. The objective of the study was to study the clinical and etiological profile of patients with unprovoked thrombosis in young patients. Methods: Twenty-one patients 09 males (42.8%) and 12 females (57.14%) with a mean age of 29.67±5.21 were studied, who presented with unprovoked thrombosis. Results: Among 21 patients studied most common presentation was deep venous thrombosis of lower limbs (38.09%) followed by recurrent abortions with deep venous thrombosis (14.28%) and cerebellar infarction (14.28%). In etiological profile, the most common thrombophilla was factor V Leiden mutation (28.57%) followed by antiphospholipid antibody syndrome (23.8%), protein C deficiency (19.04%), methylene tetrahydrofolate reductase (9.52%) and antithrombin, prothrombin gene mutation, hyperhomocystenemia and janus kinase 2 mutations (4.76%). Among 6 patients of factor V Leiden mutation 3 presented with deep venous thrombosis of lower limbs, 1 patient each with middle cerebral artery infarct, juglar vein thrombosis and subclavian vein thrombosis respectively. Conclusions: Factor V Leiden mutation is the most common inherited thrombophillias which has been "substantiated from various studies.